(untitled) (Mustansiria Dental Journal, 2018)
The purpose of this study was to compare dentinal defect formation while using hand files (HFs), two brands of nickel-titanium (NiTi) rotary files and the WaveOne file. Eighty mandibular first molars were selected and divided into 4 groups. Hand file (HFs), WaveOne reciprocating file (WO), EndoSequence file (ES), ProTaper file (PT), were used to prepare the 2 mesial canals. Roots were then sectioned 3, 6, and 9 mm from the apex, and the cut surface was observed under a microscope and checked for the presence of dentinal defects. HF group showed the lowest percentages of dentinal defects (5%). In roots prepared with the WO, ES, and PT, dentinal defects were observed in 25%, 10%, and 50% of teeth, respectively. There was a significant difference between HFs group and both of WO group and PT group (P <0.05). However, no significant difference was found between HFs group and ES group (P ≥ 0.05). Also a non significant difference was found between WO group and ES group (P ≥ 0.05). All rotary files created defects in the root dentin, whereas hand instrumentation presented with satisfactory results.